2017
DOI: 10.1136/bmjqs-2017-006632
|View full text |Cite
|
Sign up to set email alerts
|

Effects of efforts to optimise morbidity and mortality rounds to serve contemporary quality improvement and educational goals: a systematic review

Abstract: These results are encouraging for those seeking to optimise the quality and safety mission of M&M rounds. However, the inability to identify consistent educational effects suggests the investigation of M&M rounds could benefit from additional methodologies (qualitative, mixed methods) in order to understand the complex mechanisms driving learning at M&M rounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 58 publications
0
21
0
1
Order By: Relevance
“…Cabe anotar, que el rol activo, un enfoque académico y el asertividad del docente que guía la discusión, su interacción con el estudiante o personal involucrado en el caso y, los participantes en la M&M dentro de un ambiente de aprendizaje seguro, en ausencia de vergüenza, miedo y culpa, son determinantes en el éxito de la reunión como estrategia de aprendizaje (30) .…”
Section: Análisis De Los Procesos E Implementación De Las Mandmunclassified
“…Cabe anotar, que el rol activo, un enfoque académico y el asertividad del docente que guía la discusión, su interacción con el estudiante o personal involucrado en el caso y, los participantes en la M&M dentro de un ambiente de aprendizaje seguro, en ausencia de vergüenza, miedo y culpa, son determinantes en el éxito de la reunión como estrategia de aprendizaje (30) .…”
Section: Análisis De Los Procesos E Implementación De Las Mandmunclassified
“…Despite their long history, it has only been relatively recently that prospective trials have been conducted to evaluate the educational contribution of M&MCs ( 15 , 19 , 21 , 24 , 26 ). These studies have developed and tested structured approaches to M&MCs, encompassing case reporting and selection, analysis of adverse events, presentation, participation, and learning outcomes.…”
Section: Benefitsmentioning
confidence: 99%
“…Several studies have reported improvements in patient safety following the presentation of cases at M&MCs and subsequent changes in patient care and management ( 12 , 13 , 22 , 25 , 26 , 29 , 30 ). A common theme of these reports is the clear structure to the M&MC process, though the degree and extent of standardization varied.…”
Section: Benefitsmentioning
confidence: 99%
“…Morbidity and Mortality Rounds (MMRs) have long been employed in acute care hospitals to review and learn from medical errors, particularly those that resulted in significant patient harm [1‐3]. With the ever‐increasing focus on patient safety in health care, MMRs have been adopted across many specialties as a forum for critical incident review using a systems‐based approach to identify root causes of quality and safety gaps, and improve future care delivery [4‐6]. However, the literature contains only 2 reports of MMRs introduced into rehabilitation settings [7,8].…”
Section: Introductionmentioning
confidence: 99%